Achieving hostel guest satisfaction: Customer experience approach - Pietrasz, Alicja (2014)
This thesis focuses on Tourism sector (youth hostel holiday accommodation) and it is led by the marketing strategy that has been recently adopted in most sectors as well in tourism that is Relationship Marketing. Recently, youth travel is a growing sector, but there is still lack of studies related to it. The objective of this study is to identify the factors that build the customer experience within the Youth Hostel sector and investigate the factors that have impact on it. A theoretical framework was developed for this study. The customer experience has been defined according to the Shaw’s Customer Experience Hierarchy of Needs Theory. Following expectancy-disconfirmation theory of Oliver (1980), experiences were divided in expected and received by customer. The gap between what customer expects and receives is actually perceived as the obtained service, which is a base for customer satisfaction. The study utilises two surveys as data collection tools. They were distributed in five European hostels and they contained questions related to the customer needs, according to Shaw’s Theory, and were divided in four groups (as layers). The data were analysed using quantitative methods. The main practical implication of the thesis is that it provides guidelines for the hostel management, to create customer satisfaction, through improving customer experience. The results emphasize the importance of staff performance. Another finding is that the length of the stay has an important impact on the expectations of the youth travellers. People that stay longer are more involved in the hostel choice.